On Some Recently Discovered Translations from Edgar Allan Poe’s Work - by È˜tefan PeticÄƒ â€“ at the End of the 19th Century - CÄƒlina, Nicoleta (European Scientific Journal, ESJ, 2018)
The first authentic Romanian Symbolist writer - poet, novelist, playwright, journalist, sociologist, È˜tefan PeticÄƒ (1877-1904) - was also a skilled translator, as most of the Romanian writers at the end of the Nineteenth century used to be. For more than 120 years, there was no information on the translator of two volumes rendered into Romanian from Edgar Allan Poeâ€™s work and published in 1896 and, respectively, in 1897, at â€œSamitcaâ€ Publishing House in Craiova.